The Effect of STEAM Activities Based on Experiential Learning on Ninth Graders' Mental Motivation - Naela Mater; Wajeeh Daher; Fayez Mahamid (MDPI AG, 2023)
The impact of STEAM (Science, Technology, Engineering, Arts, and Math) on pupils' learning has been increasingly highlighted recently. This study aims to shed light on the effect of STEAM activities based on experiential learning on ninth graders' mental motivation and learning. The present research adopted a mixed methodology (quantitative and qualitative). The study sample consisted of 90 students divided into three groups. The tools utilized in conducting the study included California Measurement Mental Motivation, and semi-structured interviews with (10) participants. The tools' validity and reliability were verified. After data were analyzed, the findings showed statically significant differences between students' post average scores regarding mental motivation due to teaching method, and in favor of the experimental groups (face-to-face STEAM activities, online STEAM activities). This provides tangible proof for the need to include STEAM activities in school curricula to enhance learners' curiosity, problem-solving skills and self-confidence through learning, as well as their task accomplishment ability.